Pathogenic bacteria features of central line-associated bloodstream infections in ICU patients: focus on the early predictive value of neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios - Li, Yuzhen; Li, Yanyan; Wang, Jiqin; Sun, Keyu (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveExplore and analyze CLABSI pathogenic bacteria characteristics in ICU patients and the value of PCT, NLR, PLR in early infection prediction.Methods926 ICU patients with central venous catheters in Minhang Hospital from January 2021 to December 2023 were enrolled. They were grouped by co-infection status. PCT, NLR and PLR levels were measured, patient data analyzed, pathogenic bacteria characteristics summarized, and their predictive value evaluated via ROC curve.ResultsFrom January 2021 to December 2023, among the 926 patients with CVC, 73 were diagnosed with CLABSI, with an infection rate of 7.88%. A total of 81 strains of pathogenic bacteria were isolated, including 60.50% (49/81) Gram - positive bacteria, 35.80% (29/81) Gram - negative bacteria, and 3.70% (3/81) fungi. The main Gram - positive bacteria exhibited high resistance to penicillin, erythromycin, clindamycin, and oxacillin, with a resistance rate exceeding 70%, yet were sensitive to vancomycin, linezolid, and tetracycline. The main Gram - negative bacteria had high resistance to piperacillin, piperacillin/tazobactam, Aztreonam, and gentamicin, with a resistance rate over 70%, and were more sensitive to cefoperazone/sulbactam, imipenem, and amikacin. Age, the site of catheterization, the duration of catheterization, and the employment of double - cavity catheters were all factors that exerted an influence on CLABSI among ICU patients (with p < 0.05). The levels of peripheral blood NLR, PLR, and PCT in the infected group were higher than those in the non - infected group (p < 0.05). The areas under the curve (AUCs) of peripheral blood NLR, PLR, and PCT were 0.814, 0.798, and 0.856, respectively, with the largest AUC for PCT. When the cut - off point was 2.75 ng/ml, the Youden index was the largest. The AUCs of the combination of peripheral blood NLR and PLR, NLR and PCT, PLR and PCT, and all three combined were 0.877, 0.903, 0.857, and 0.917.ConclusionThe early prediction of CLABSI in ICU patients by means of PCT, NLR, and PLR is of remarkable significance. It can provide a precious reference for clinical diagnostic and treatment strategies.